Role of cathepsin S In periodontal wound healing-an in vitro study on human PDL cells - Memmert, Svenja; Nokhbehsaim, Marjan; Damanaki, Anna; Nogueira, Andressa V.B. [UNESP]; Papadopoulou, Alexandra K.; Piperi, Christina; Basdra, Efthimia K.; Rath-Deschner, Birgit; Götz, Werner; Cirelli, Joni A. [UNESP]; Jäger, Andreas; Deschner, James (Springer Nature, 2018)
Background: Cathepsin S is a cysteine protease, which is expressed in human periodontal ligament (PDL) cells under inflammatory and infectious conditions. This in vitro study was established to investigate the effect of cathepsin S on PDL cell wound closure. Methods: An in vitro wound healing assay was used to monitor wound closure in wounded PDL cell monolayers for 72h in the presence and absence of cathepsin S. In addition, the effects of cathepsin S on specific markers for apoptosis and proliferation were studied at transcriptional level. Changes in the proliferation rate due to cathepsin S stimulation were analyzed by an XTT assay, and the actions of cathepsin S on cell migration were investigated via live cell tracking. Additionally, PDL cell monolayers were treated with a toll-like receptor 2 agonist in the presence and absence of a cathepsin inhibitor to examine if periodontal bacteria can alter wound closure via cathepsins. Results: Cathepsin S enhanced significantly the in vitro wound healing rate by inducing proliferation and by increasing the speed of cell migration, but had no effect on apoptosis. Moreover, the toll-like receptor 2 agonist enhanced significantly the wound closure and this stimulatory effect was dependent on cathepsins. Conclusions: Our findings provide original evidence that cathepsin S stimulates PDL cell proliferation and migration and, thereby, wound closure, suggesting that this cysteine protease might play a critical role in periodontal remodeling and healing. In addition, cathepsins might be exploited by periodontal bacteria to regulate critical PDL cell functions.
Keywords: Cathepsin S; Migration; Periodontal ligament cells; Wound closure